Efficacy and safety of interim oncology treatments introduced for solid cancers during the COVID-19 pandemic in England: a retrospective evidence-based analysisResearch in context - Mark P. Lythgoe; Alica-Joana Emhardt; Huseyin Naci; Jonathan Krell; Richard Sullivan; Ajay Aggarwal (Elsevier, 2024)
Summary: Background: The COVID-19 global pandemic placed unprecedented pressure on cancer services, requiring new interim Systemic Anti-Cancer Treatments (SACT) options to mitigate risks to patients and maintain cancer services. In this study we analyse interim COVID-19 SACT therapy options recommended in England, evaluating the evidence supporting inclusion and delineating how these have been integrated into routine cancer care. Methods: We performed a retrospective analysis of interim Systemic Anti-Cancer Treatments endorsed by NHS England during the COVID-19 pandemic. Interim therapy options were compared to baseline (replacement) therapies by comparing data from the key pivotal trial(s) in terms of clinical efficacy and potential benefits (e.g., reduced immunosuppression or improved adverse effect profile) within the context of the pandemic. Furthermore, we evaluated the evolution of these interim SACT options, exploring if these have been integrated into current treatment pathways or are no longer accessible at the pandemic end. Findings: 31 interim oncology treatment options, across 36 indications, for solid cancers were endorsed by NHS England between March 2020 and August 2021. Interim therapies focused on the metastatic setting (83%; 30/36), allowing greater utilisation of immune checkpoint inhibitors (45%; 14/31) and targeted therapies (26%; 8/31), in place of cytotoxic chemotherapy. Overall, 36% (13/36) of therapies could not have efficacy compared with baseline treatments due to a paucity of evidence. For those which could, 39% (9/23) had superior efficacy (e.g., overall survival), 26% (6/23) had equivocal efficacy and 35% (8/23) lower efficacy. 53% (19/36) of interim therapies had better or equivocal toxicity profiles (when assessable), and/or were associated with reduced immunosuppression. Almost half (47%; 17/36) of interim therapies did not have UK market authorisation, being classified as 'off label' use. Analysing access to interim options at the end of the pandemic (May 2023) identified 19 (53% 19/36) interim options were fully available, and a further four (11% 4/36) therapies were partially available. Interpretation: Interim SACT options, introduced in England, across a range of solid cancers supported delivery of cancer services during the pandemic. Most interim therapies did not demonstrate superior efficacy, but provided other important benefits (e.g., reduced immunosuppression) in the context of the pandemic. Funding: None.